2016
DOI: 10.1007/s13346-016-0282-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term stability of influenza vaccine in a dissolving microneedle patch

Abstract: This study tested the hypothesis that optimized microneedle patch formulations can stabilize trivalent subunit influenza vaccine during long-term storage outside the cold chain and when exposed to potential stresses found during manufacturing and storage. Formulations containing combinations of trehalose/sucrose, sucrose/arginine, and arginine/heptagluconate were successful at retaining most or all vaccine activity during storage at 25°C for up to 24 months as determined by ELISA assay. The best formulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(74 citation statements)
references
References 36 publications
1
67
0
1
Order By: Relevance
“…The formulation exhibited superior immune response compared to the same dose via intramuscular injection. [46][47][48] In addition, the same research group used these microneedles made using polyvinyl alcohol and sucrose to successfully deliver tetanus, rabies and ebola vaccines along with synthetic vaccines made of layer-by-layer microparticles against respiratory syncytial virus. [49][50][51][52] On the other hand, Donnelly et al used "super swelling" microneedles made of hydrogel forming polymers (Gantrez S-97, polyethylene glycol and Na 2 CO 3 ) to deliver 0.32 g OVA across the skin of Sprague Dawley rats.…”
Section: Discussionmentioning
confidence: 99%
“…The formulation exhibited superior immune response compared to the same dose via intramuscular injection. [46][47][48] In addition, the same research group used these microneedles made using polyvinyl alcohol and sucrose to successfully deliver tetanus, rabies and ebola vaccines along with synthetic vaccines made of layer-by-layer microparticles against respiratory syncytial virus. [49][50][51][52] On the other hand, Donnelly et al used "super swelling" microneedles made of hydrogel forming polymers (Gantrez S-97, polyethylene glycol and Na 2 CO 3 ) to deliver 0.32 g OVA across the skin of Sprague Dawley rats.…”
Section: Discussionmentioning
confidence: 99%
“…The use of biomaterials are a central part of novel strategies to develop next-generation vaccines [19,20], delivery systems [21,22] with improved thermostability [23].…”
Section: Introductionmentioning
confidence: 99%
“…A better understanding of the vaccine stability throughout the fabrication, storage and administration process is essential for the future optimization [94]. Appropriate formulation methods using MN patch preserve the long-term antigen immunogenicity and allow flexible storage conditions [95]. To assess the effect of the coating formulation to the stability of viral proteins, Zhu et al suspended the viral proteins in a coating solution and found the experimental responses were comparable with the control groups in terms of antibody production [96].…”
Section: Types Of Delivered Proteinmentioning
confidence: 99%